Hispanicism and early US literature : Spain, Mexico, Cuba, and the origins of US national identity - Havard, John C. (The University of Alabama Press, 2018)
Well-researched analysis of the impact that Spain and Spanish America had on antebellum literature in the United States. In Hispanicism and Early US Literature, author John C. Havard posits that representations of Spain, Spanish America, Spanishness, and Spanish Americanness are integral elements in the evolution of early national and antebellum US literature. He argues that Spanish-speaking countries have long held a broad fascination for Americans and that stock narratives regarding these peoples were central to the period's US literature. Beginning with the work of eighteenth-century literary nationalists such as Joel Barlow, US literature has been drawn to reflect on Spain and Spanish America. Such reflection was often inspired by geopolitical conflicts such as US expansion into Spanish Louisiana and the US-Mexican War. Havard terms the discourse emerging from these reflections "Hispanicism." This discourse was used to portray the dominant viewpoint of classical liberalism that propounded an American exceptionalism premised on the idea that Hispanophone peoples were comparatively lacking the capacity for self-determination, hence rationalizing imperialism. On the conservative side were warnings against progress through conquest. Havard delves into selected works of early national and antebellum literature on Spain and Spanish America to illuminate US national identity. Poetry and novels by Joel Barlow, James Fenimore Cooper, and Herman Melville are mined to further his arguments regarding identity, liberalism, and conservatism. Understudied authors Mary Peabody Mann and José Antonio Saco are held up to contrast American and Cuban views on Hispanicism and Cuban annexation as well as to develop the focus on nationality and ideology via differences in views on liberalism. More than just a work of literary criticism, there is a substantial amount of cultural and political history discussed. Havard's use of archival sources such as political articles and personal correspondence elucidates not just literary genres and movements such as early national epic poetry, abolitionist fiction, and the American Renaissance, but also US culture writ large.